Profil Fitokimia Tanaman Johar - Mardanis S (Balai Besar Kimia dan Kemasan, 1996)
Investigation on phytochcmieal of Johar species (Cassia siamca, Lam.k) has been done. Alkaloid content about 0,05 % is obtained by qualitative and quantitative analysis. The methanol are used as solvent in the alkaloid extraction. Cri.stalization from that extract yield a yellow crystal, with melting point 218 - 220 °C. Reference factor (Rf) value is 0,49 in methanol - benzena ( 1 : 9 ) solvent. The analysis of the infrared spectrometry indicated that the compound containing hydroxyl group which attached into the aromatic ring and amine group located in the aromatic ring, with the absorbtion peak about 3250 cm, C = C (1620 cm